Carrot and stick: how RNase R contributes to function and destruction of the translation machinery - Helge Paternoga; Lyudmila Dimitrova-Paternoga (RNA Biology)
RNA is fundamental for life, and its homoeostasis is a critical contributor to cellular growth and adaptation to stress. Key RNA species include messenger RNA (mRNA) and non-coding RNAs, such as transfer RNA (tRNA), or ribosomal RNA (rRNA), that are essential for ribosome formation and translation of the genetic code. Furthermore, various other non-coding RNAs are expressed at each growth stage. Given RNA’s abundance and its role in all cellular processes, RNases – enzymes responsible for RNA degradation and processing – are central to RNA metabolism. In this review, we discuss the pivotal contribution of the 3’ exonuclease RNase R to bacterial RNA homoeostasis. We focus on its functions in regulating and degrading components of the translation machinery, including the trans-translation system, and we take a look at recent structural studies that shed new light on the activities of this important enzyme.